MicroRNA-122 regulates caspase-8 and promotes the apoptosis of mouse cardiomyocytes - Zhang,Z.W. (2017)
Cardiomyocyte apoptosis plays key roles in the pathogenesis of heart diseases such as myocardial infarction. MicroRNAs are important regulators of gene expression, which are also involved in the regulation of cardiomyocyte apoptosis. However, cardiomyocyte apoptosis regulated by microRNA (miR)-122 is largely unexplored. The aim of this study focused on the role of miR-122 in cardiomyocyte apoptosis. Cardiomyocytes were isolated from neonatal mice and primarily cultured. MiR-122 mimic and inhibitor were transfected to cardiomyocytes and verified by qRT-PCR. Cell viability and apoptosis post-transfection were assessed by MTT assay and flow cytometry, respectively. Changes in expression of caspase-8 were quantified by qRT-PCR and western blot. Results showed that miR-122 mimic and inhibitor successfully induced changes in miR-122 levels in cultured cardiomyocytes (P<0.01). MiR-122 overexpression suppressed viability and promoted apoptosis of cardiomyocytes (P<0.05), and miR-122 knockdown promoted cell viability and inhibited apoptosis (P<0.05). The mRNA and protein levels of caspase-8 were elevated by miR-122 overexpression (P<0.01) and reduced by miR-122 knockdown (P<0.001). These results suggest an inductive role of miR-122 in cardiomyocyte apoptosis, which may be related to its regulation on caspase-8.